Chromosomal location of human T-cell receptor gene Ti beta. - Barker, P; Ruddle, F; Royer, H; Acuto, O; Reinherz, E (1984)
A complementary DNA probe corresponding to the beta-chain gene of Ti, the human T lymphocyte receptor, has been molecularly cloned. The chromosomal origin of the Ti beta gene was determined with the complementary DNA by screening a series of 12 cell hybrid (mouse X human) DNA's containing overlapping subsets of human chromosomes. DNA hybridization (Southern) experiments showed that the human Ti beta gene resides on chromosome 7 and is thus not linked to the immunoglobulin loci or to the major histocompatibility locus in humans.